Neonatal renal function assessment. Issue 9 (September 1989) - Clark, P M; Bryant, T N; Hall, M A; Lowes, J A; Rowe, D J
Abstract : Urine samples from neonates admitted to a special care baby unit were analysed to establish ranges for urinary retinol binding protein, albumin, and total protein concentrations in healthy term and preterm infants and to investigate changes seen in disease states. Urinary excretion of retinol binding protein was greater in preterm infants and was increased in sick infants. This was greater than would be predicted from changes in creatinine excretion with gestational or postconceptional age. Urinary retinol binding protein appeared more sensitive to illness than did urinary albumin or total protein.